MODEL BISNIS BERKELANJUTAN ERA MODERN KAJIAN HUKUM EKONOMI SYARIAH - Anisa, Darania (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study discusses the importance of implementing a sustainable business model in accordance with the principles of Islamic economic law in the modern era. The main issues raised are the increasing violations of business ethics due to unfair competition and lack of attention to social and environmental sustainability in business activities. The formulation of the problem in this study includes how a sustainable business model can be implemented in accordance with Islamic principles to overcome these challenges. The purpose of the study is to provide guidance on the implementation of Islamic business ethics as a foundation in building a sustainable business model that is able to answer global needs. The research method used is a literature study with a qualitative approach, relying on secondary data from various literature sources related to the digital economy and Islamic business ethics. The results of the study indicate that a sustainable business model can be implemented by strengthening the principles of justice, transparency, and avoiding practices that violate Islamic law such as usury, maysir, and gharar. In addition, the triple bottom line approach (profit, people, planet) integrated with Islamic values is able to create economic, social, and environmental sustainability. This article emphasizes the importance of compliance with Islamic principles and the role of supervisory institutions in ensuring ethical and just business sustainability.